Energy Market Integration and Energy Poverty in ASEAN - Adoracion M. Navarro; Maxensius Tri Sambodo; Jessie L. Todoc (Philippine Institute for Development Studies (PIDS), 2013)
Based on available statistics, between 127 and 130 million people in Southeast Asia lack access to electricity. At least 228 million still rely on traditional biomass for cooking and lack access to clean and modern cooking facilities, with dire consequences for their quality of life and human development. Discussions for an integrated Association of Southeast Asian Nations (ASEAN) energy market cannot overlook this energy poverty situation in the region. In fact, the overall goal of ASEAN Energy Market Integration (AEMI) to achieve balanced and equitable economic growth and development for all countries in the region cannot be realized while people continue to suffer from energy poverty. This study maps the energy poverty situation in the region, and reviews the links between energy access and economic and human development. It also draws a connection between AEMI and the eradication of energy poverty, or attaining universal energy access, in terms of benefits and strategies, particularly with regard to mapping investment requirements and taking inventory of financing options. The study concludes with some recommendations for near-term actions.
Keywords: 330; ASEAN; energy market integration; energy poverty; electrification; universal access